2013
DOI: 10.1016/j.bbr.2013.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical enhancement of fear expression and extinction deficits in mice resilient to social defeat

Abstract: The exposure to stress has been associated with increased depressive and anxiety symptoms, yet not all individuals respond negatively to the experience of stress. Recent rodent social defeat models demonstrate similar individual differences in response to social stress. In particular, mice subjected to chronic social defeat have been characterized as being either "susceptible" or "resilient" by the level of social interaction following social defeat. Susceptibility is associated with lasting social avoidance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…Similar to non-stressed mice, resilient animals remained in the interaction zone for a longer period when the target was present than when it was absent; however, susceptible subjects remained in the interaction zone for less time and spent longer periods in the corner zones when there was social stimuli. These data are consistent with previous studies [8, 37, 53] in which the social defeat stress paradigm induced two phenotypic responses during a subsequent social interaction test: resilient mice did not display a decrease in social interaction after social defeat, in a similar way to the non-stressed group, whereas susceptible mice were characterized by prolonged social avoidance, even though all animals had an identical genetic background and all had been exposed to similar conditions of social defeat stress. Therefore, resilient animals displayed a similar behavioral pattern to that of non-stressed mice.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to non-stressed mice, resilient animals remained in the interaction zone for a longer period when the target was present than when it was absent; however, susceptible subjects remained in the interaction zone for less time and spent longer periods in the corner zones when there was social stimuli. These data are consistent with previous studies [8, 37, 53] in which the social defeat stress paradigm induced two phenotypic responses during a subsequent social interaction test: resilient mice did not display a decrease in social interaction after social defeat, in a similar way to the non-stressed group, whereas susceptible mice were characterized by prolonged social avoidance, even though all animals had an identical genetic background and all had been exposed to similar conditions of social defeat stress. Therefore, resilient animals displayed a similar behavioral pattern to that of non-stressed mice.…”
Section: Discussionsupporting
confidence: 92%
“…The relationship of resilient vs. susceptible phenotypes to learned fear behavior has recently begun to be studied, but a clear picture has not yet emerged: Chou et al. (2014) found that susceptible mice exhibited greater freezing during fear conditioning compared to a resilient population, while Meduri et al. (2013) previously reported that resilient animals expressed higher and longer-sustained fear levels.…”
Section: Effects Of Stress On Learned Fearmentioning
confidence: 99%
“…A commonly used chronic stress paradigm is chronic mild unpredictable stress, which has both face validity in producing symptoms and predictive validity for response to antidepressants in rats [13]; however, the effects of this paradigm in mice have been less consistent [6,7]. Social defeat is another commonly used stress paradigm in rats [11], but a percentage of mice are resistant to the negative effects of chronic social defeat [1416]. An alternative chronic stress paradigm is the use of predatory stress, which is more potent than exposure to chronic mild unpredictable stress in mice [17].…”
Section: Introductionmentioning
confidence: 99%